Electrical Properties of a Ga0.952In0.048N0.016As0.984 p-i-n Schottky Barrier Diode - Muhammad Izzuddin Abd Samad; Mohammad Syahmi Nordin; Nafarizal Nayan; Afishah Alias; Adrian Boland-Thoms; Anthony John Vickers; Khairul Anuar Mohamad; Marinah Othman (The Academy of Sciences Malaysia, 2024)
ASM Sc. J., 12, Special Issue 4, 2019 for ICSE2018, 131-138